The Special Relationship: The US, Great Britain and Egypt over the Suez Canal - Sanghro, Rafi Raza; Chandio, Jalil Ahmed; Soomro, Siraj Ahmed (Journal of History Culture and Art Research, 2018)
The United Kingdom had ruled nearly the whole world. It is said that the sun never sets on the British Empire. The emergence of World War I and II weaken the power of Britain as a dominate colony of the world. However, by the end of WW-II, the US emerged as the newly famous, powerful country in the world. During the WW-II, the UK and the USA developed close cooperation. The relationship of both countries developed to such an extent that the Prime Minster W.D. Churchill called it the Special Relationship between UK-USA. The special relationship between both nations continued after the end of WW-II. It was believed that the bond of relationship is so strong that it cannot be rifted. It was right considering the close cooperation between both countries during the WW-II and aftermaths. However, the incident of the Suez Canal in 1956, completely changed the scenario. The tension between both states appeared over the Suez Crisis. This historical analysis is made to understand to what extent the special relationship was strong? Moreover, what went wrong during the Suez Crisis that shattered the special relationship between UK-USA. Was the Suez debacle of 1956, served as the litmus test paper in examining the special relationship?